The Victory of the Female Regent of Grobogan Regency Judging from Robert Putnam's Theory - Suneki, Sri; Larasati, Endang; Yuwanto, Yuwanto; Fitriyah, Fitriyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The winning capital according to Robert Putnam's theory includes network capital, norms, and trust. This study aims to analyze the victory of the Female Regent of Grobogan Regency based on Robert Putnam's theory. This study used the descriptive qualitative method. This study uses primary data from in-depth interviews with the female regent of Grobogan Regency, the Secretary of the DPC PDI-P as the supporting party, educational leaders, religious leaders, and voters. Secondary data were obtained from documents, reports from the General Elections Commission, and articles about the winners of female regent candidates in the Grobogan Regency. The findings of this study are the victory of the Regent of Women in Grobogan Regency is in line with Robert Putnam's theory because of social network capital, norm capital, and trust from the community. New in this study there is additional capital that is not part of Robert Putnam's theory, namely the capital profile of a motherly candidate and the nickname "Sri Pupuk".